GcSTUA, an APSES Transcription Factor, Is Required for Generation of Appressorial Turgor Pressure and Full Pathogenicity of Glomerella cingulata - XingZhang Tong; Xiuwen Zhang; Kim M. Plummer; Kathryn M. Stowell; Patrick A. Sullivan; Peter C. Farley (Molecular Plant-Microbe Interactions, 2007)
Glomerella cingulata, which infects a number of different hosts, gains entry to the plant tissue by means of an appressorium. Turgor pressure generated within the appressorium forces a penetration peg through the plant cuticle. A visible lesion forms as the fungus continues to grow within the host. A G. cingulata homolog (GcSTUA) of the genes encoding Asm1, Phd1, Sok2, Efg1, and StuA transcription factors in Magnaporthe grisea and other fungi was cloned and shown to be required for infection of intact apple fruit and penetration of onion epidermal cells. Mobilization of glycogen and triacylglycerol during formation of appressoria by the GcSTUA deletion mutant appeared normal and melanization of the maturing appressoria was also indistinguishable from that of the wild type. However, GcSTUA was essential for the generation of normal turgor pressure within the appressorium. As is the case for its homologs in other fungi, GcSTUA also was required for the formation of aerial hyphae, efficient conidiation, and the formation of perithecia (sexual reproductive structures).